RANCANG BANGUN SISTEM SUPPLY CHAIN MANAGEMENT MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) PADA PT SUGIH BOGA NUSANTARA - Subhan Ali Kahar; Ari Syaripudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Supply Chain Management is a network of organizations and business processes for procuring raw materials, converting materials into semi-finished products and finished products, then distributing finished products to customers.The inventory information system using the Rapid Application Development method is expected to be able to overcome the problem of documents that are prone to loss, because the goods report can be viewed directly by the head of the warehouse through software, able to avoid typing errors in processing goods data.